RANCANG BANGUN RUANG PENYIMPANAN BIBIT BAWANG MERAH SIAP TANAM MENGGUNAKAN BOARD ESP32 BERBASIS INTERNET OF THINGS - deny hardiansya putra makrup; Amalia Herlina; Fuad Hasan (Universitas Tarumanagara, 2022)
Pondokkelor Village is one of the many areas in Probolinggo Regency which is a producer of shallots, in the nursery process the farmers buy seeds outside the area and do not produce them because of frequent failures in the growth process. Seeds that have been purchased will be stored in a dry room or warehouse and not damp within 1 to 2 months. In the process of storing shallot seeds, it will experience shrinkage so that it can affect the planting process, with this study which aims to compare the weight of shallot seeds stored for 30 days using conventional methods and storage box boxes that have been equipped with an IoT-based control system (Internet of things). This storage box is equipped with a DHT22 Sensor which functions to read the temperature in the storage room box and a Loadcell Sensor that functions to read the weight of the value on the seeds, as well as the Blynk Application which functions to monitor the shrinkage value of onion seedlings every day. If the reading of the temperature value on the DHT22 sensor is less than 26 degrees Celsius, the light bulb will turn on automatically and if the temperature value is more than 32 degrees Celsius, the fan will turn on. Sampling was done by placing shallot seeds on loadcell scales in a box and loadcell scales in an open room as much as 501 grams. From the results of research for 30 days, conventional storage methods have a difference in the average value of depreciation of 8.93 per day with IoT-based storage boxes and 11 grams of seed weight difference, so it can be concluded that the use of IoT-based storage boxes is more effective than conventional use.